Morphosyntactic and morphophonological variation in Breton: a cross-generational perspective. Issue 2 (July 2019) - Kennard, Holly
Abstract: Like France's other regional languages, Breton has seen a steep decline, followed by a period of revitalization in recent decades. Today there are two largely separate communities of speakers: older, traditional speakers who grew up speaking Breton at home, and younger speakers, generally from French-speaking homes, most of whom have learnt Breton through immersion schooling. It is claimed that this 'Neo-Breton' differs from the language of older speakers, lexically, phonologically and grammatically. This article examines morphosyntactic (impersonal) and morphophonological (mutation) data to explore exactly how Neo-Breton differs from that of traditional speakers, and how the variability in the data might be explained. The data show that contrary to what might be expected, new speakers do not differ greatly from older, traditional speakers in these areas. Influence from French is more subtle than might be supposed. Children and teenagers who attend Breton-medium schooling seem to show an extended period of acquisition, but the data from adult new speakers suggests that with enough Breton input, these young speakers can reach full proficiency. However, as the number of older speakers decreases, Breton seems likely to see more widespread language change.